A Snapshot on the Distribution of Coastal Phytoplankton Communities in Five HAB-Affected Bays in Eastern Visayas, Philippines - Ravelo, Stephanie Faith; Yap-Dejeto, Leni G.; Silaras, Mark Leonard S.; Amparado, Ma. Luningning L.; Ocampo, Jason A.; Abria, Eugene G.; Albina, Marietta B. (Frontiers in Marine Science, 2022)
In recent years, harmful algal blooms (HABs), commonly known as red tide, have started to occur year-round in the warm tropical marine waters of Eastern Visayas, Philippines. These are a threat to public safety and cause enormous loss in industries relying on marine resources. The first step in solving this problem is to establish the distribution and succession of phytoplankton communities and harmful microalgae that exist in the region. For the first time, simultaneous monthly monitoring of the phytoplankton community was conducted in five HAB-affected bays of Leyte and Samar islands. We observed spatial differences on the environmental profiles between the five bays in the two islands and these differences may, in part, influence the distribution and abundance of the phytoplankton community residing within these areas. Diatom associated groups were prevalent in all sampling sites, however, HAB causative species were abundant in the bays in Samar during the sampling period. Five (5) genera and nine (9) species that may cause HAB were identified in all five bays. These are potential vectors for paralytic shellfish poisoning, amnesic shellfish poisoning, diarrhetic shellfish poisoning, and fish kill due to hypoxia. The correlation analysis confirmed that the majority of potential HAB vectors correlated with temperature, dissolved oxygen, rainfall, nitrate, and phosphate. The abundance of Pyrodinium bahamense observed in October to November in Samar coincided with several red tide alerts announced by the region’s fishery agency. This however, was never observed to dominate the phytoplankton community. Instead, the following diatoms dominated the five bays; Skeletonema, Pseudo-nitzschia, Bacteriastrum, Chaetoceros, Rhizosolenia and Thalassionema. This is a pioneering study that shows a simultaneous snapshot on the community structure and environmental profiles in these five bays in Eastern Visayas in 2020–2021. It discusses the effects of mariculture to its phytoplankton community and vice versa. Relationships between different phytoplankton species were further observed. This contributes to the knowledge of phytoplankton ecology in warm waters which is necessary to understand future phytoplankton ecosystems affected by sea temperature rise due to climate change.